Activities of Therapeutic Agents and Myristamidopropyl Dimethylamine against Acanthamoeba Isolates - Kilvington, Simon (American Society for Microbiology, 2002)
The activities of therapeutic agents and myristamidopropyl dimethylamine (MAPD) against Acanthamoeba strains recalcitrant to medical therapy were studied. MAPD minimum cysticidal concentrations were 6.25 to 25 μg/ml; 10 to 30 μg/ml gave at least a 3-log cyst kill after 6 h, and 50 and 100 μg/ml gave at least a 3-log cyst kill within 2 and 1 h, respectively.